Effect of Spatial Structure Defined by Binocular Disparity with Uniform Luminance on Lightness. (January 2020) - Kanari, Kei; Kaneko, Hirohiko
We examined whether lightness is determined based on the experience of the relationship between a scene's illumination and its spatial structure in actual environments. For this purpose, we measured some characteristics of scene structure and the illuminance in actual scenes and found some correlations between them. In the psychophysical experiments, a random-dot stereogram consisting of dots with uniform distribution was used to eliminate the effects of local luminance and texture contrasts. Participants matched the lightness of a presented target patch in the stimulus space to that of a comparison patch by adjusting the latter's luminance. Results showed that the matched luminance tended to increase when the target patch was interpreted as receiving weak illumination in some conditions. These results suggest that the visual system can probably infer a scene's illumination from a spatial structure without luminance distribution information under an illumination–spatial structure relation.